2003
DOI: 10.1136/tc.12.suppl_4.iv11
|View full text |Cite
|
Sign up to set email alerts
|

A randomised clinical trial of nicotine patches for treatment of spit tobacco addiction among adolescents

Abstract: Background: This study tested the efficacy of nicotine patches in combination with behavioural therapy for the treatment of adolescent spit tobacco addiction. Prior interventions had resulted in mean cessation rates below 15% at one year. Methods: This study, the PATCH Project, used a three group, placebo controlled, randomised clinical trial design. The control group received a standard 3-5 minute counselling followed by a two week follow up phone call. The two intervention groups received a six week behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…[152][153][154][155] Assessment of nicotine dependence among adolescents has been difficult and controversial because of the varying subjective criteria used for defining dependence and the widely varying sample characteristics. 156,157 Unlike adults, adolescent smokers are also more likely to be influenced by behavioral and social factors than addiction to nicotine.…”
Section: Table 3 Proposed Tobacco Control Objectives For Chronically mentioning
confidence: 99%
“…[152][153][154][155] Assessment of nicotine dependence among adolescents has been difficult and controversial because of the varying subjective criteria used for defining dependence and the widely varying sample characteristics. 156,157 Unlike adults, adolescent smokers are also more likely to be influenced by behavioral and social factors than addiction to nicotine.…”
Section: Table 3 Proposed Tobacco Control Objectives For Chronically mentioning
confidence: 99%
“…Other nicotine patch trials for adolescent smoking cessation have failed to show significant differences among treatment groups. [14][15][16][17] Bupropion hydrochloride, the first nonnicotine medication approved for smoking cessation, was an important advance in adult treatment of tobacco dependence and has been studied in 2 recent cessation trials for adolescents. An open-label feasibility study of sustained-release (SR) bupropion hydrochloride in adolescents with comorbid attentiondeficit/hyperactivity disorder (ADHD) and nicotine dependence showed significant decreases in cigarettes smoked (PϽ.001) and carbon monoxide levels (P=.04) during the course of 6 weeks of treatment (150 mg twice daily), and abstinence rates of 31.25% after 4 weeks of treatment.…”
mentioning
confidence: 99%
“…Results from other smokeless tobacco trials have reported the value of NRT in reducing withdrawal symptoms and NRT-related adverse events during quit attempts [13][14][15][16][17][18][19]. Participant satisfaction with English NHS SSS has been reported previously to be high [23,33].…”
Section: What Is Already Knownmentioning
confidence: 92%
“…NRT patch and gum use was observed to reduce withdrawal symptoms both in range and intensity compared to placebo. NRT-related adverse events were reported as minimal, more likely to be heartburn or gastroesophageal reflux if lozenges were used [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%